2008
DOI: 10.1177/1087054707308468
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of the Quality of Life Enjoyment and Satisfaction Questionnaire—Short Form in Adults With ADHD

Abstract: These results support the validity of the Q-LES-QSF as a measure of quality of life in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 14 publications
4
65
0
1
Order By: Relevance
“…The fact that the Q-LES-Q(SF) does not represent a GAD-specific patient-reported measure of QOL is another potential limitation. However, the validity of the Q-LES-Q has been convincingly demonstrated across psychiatric disorders (Endicott et al 1993;Ritsner et al 2005;Rossi et al 2005;Endicott et al 2006;Schechter et al 2007;Mick et al 2008;Revicki et al 2008). As an exploratory secondary data analysis, no method to control for the probability of family-wise type I error due to multiple comparisons planned was incorporated beyond Scheffe's method as mentioned for overall comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the Q-LES-Q(SF) does not represent a GAD-specific patient-reported measure of QOL is another potential limitation. However, the validity of the Q-LES-Q has been convincingly demonstrated across psychiatric disorders (Endicott et al 1993;Ritsner et al 2005;Rossi et al 2005;Endicott et al 2006;Schechter et al 2007;Mick et al 2008;Revicki et al 2008). As an exploratory secondary data analysis, no method to control for the probability of family-wise type I error due to multiple comparisons planned was incorporated beyond Scheffe's method as mentioned for overall comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), in both the long and short form (Q-LES-Q(SF)), is a widely used instrument for measuring QOL and satisfaction. Originally developed for use in clinical trials and among trial participants with a wide variety of mental and medical diseases or disorders (Endicott et al 1993), it has been shown to offer high internal consistency, validity and reproducibility in non-psychiatric populations and in patients with a range of psychiatric illnesses (Endicott et al 1993;Ritsner et al 2005;Rossi et al 2005;Endicott et al 2006;Schechter et al 2007;Mick et al 2008;Revicki et al 2008). Thus, the Q-LES-Q(SF) is a PRO measure that has the potential to extend and complement clinical efficacy endpoints and demonstrate the impact of alleviating GAD symptoms on patients' everyday functioning.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Quality-of-life is negatively correlated with symptom severity. 8,11,12 Information on the impact of treatment on the broad range of life impairments, behaviors, and sleep or insomnia in adults with ADHD is limited.…”
mentioning
confidence: 99%
“…La suma de las escalas crea el Q-LES-Q total de satisfacción con la vida. El instrumento tiene una consistencia interna adecuada (0.88) y validez concordante con ajuste social (0.72) (Mick, Faraone, Spencer, Zhang, & Biederman, 2008).…”
Section: Relaciones Entre Funciones Ejecutivas Y Calidad De Vida De Junclassified